Applied science in the casting of metals - Strauss, K. (Pergamon Press, 1970)
Applied Science in the Casting of Metals focuses on metallurgical operations. The book first discusses the manufacture of iron and steel. Concerns include treatment of liquid iron and steel; treatment of molten iron between blast furnace and steelworks; and treatment of liquid steel. The text takes a look at casting pit practice, including ingot feeding, hot topping of alloy steels, methods of applying hot-tops, and hot-topping methods. The selection focuses on spray steel making and continuous casting of steel. The process involved in spray steel making; the basic principles of casting of ste.